Bond graph modeling of soft switching concept and its parameters optimization. (2nd October 2019) - Mahato, Anil C.; Ghoshal, Sanjoy K.; Samantaray, Arun K.
ABSTRACT: The function of a soft switch is to provide a temporarily flow path of high pressure throttle fluid and store it temporally in a small chamber during valve transition, thus leading to passive vibration isolation. In this article, three different on/off controlled hydraulic systems without and with soft switch have been modeled using bond graph technique and simulated to analyze the performance of the soft switch. Some key parameters of the soft switch are identified and their values are optimized through multiple-run simulation. Thereafter, a relationship has been derived between the soft switch parameters and the overall energy loss of the system using regression analysis. It has been observed that the total energy loss in the system with soft switch is about one-third of that when the system is operated with relief valve only.